Node.js, MongoDB, and AngularJS Web Development - Dayley, Brad (Addison-Wesley Professional, 2014)
Node.js, MongoDB and AngularJS Web Development The definitive guide to building JavaScript-based Web applications from server to browser Node.js, MongoDB, and AngularJS are three new web development technologies that together provide an easy to implement, fully integrated web development stack. Node.js is a leading server-side programming environment, MongoDB is the most popular NoSQL database, and AngularJS is quickly becoming the leading framework for MVC-based front-end development. Together they allow web programmers to create high-performance sites and applications built completely in JavaScript, from server to client. Node.js, MongoDB and AngularJS Web Development is a complete guide for web programmers who want to integrate these three technologies into full working solutions. It begins with concise, crystal-clear tutorials on each of the three technologies and then quickly moves on to building several common web applications. Readers will learn how to use Node.js and MongoDB to build more scalable, high-performance sites, how to leverage AngularJS's innovative MVC approach to structure more effective pages and applications, and how to use all three together to deliver outstanding next-generation Web solutions. Implement a highly scalable and dynamic web server using Node.js and Express Build server-side web services in JavaScript Implement a MongoDB data store for your web applications Access and interact with MongoDB from Node.js JavaScript code Define static and dynamic web routes and implement server-side scripts to support them Implement Express in Node.js Create Jade templates Define your own custom AngularJS directives that extend the HTML language Implement client-side services that can interact with the Node.js web server Build dynamic browser views that provide rich user interaction Add authenticated user accounts to your web applications Add nested comment components to your web pages Build an end-to-end shopping cart